Marijuana and Breastfeeding. Issue 1 (January 2022) - Spatz, Diane L.
Abstract : Marijuana use among adults of childbearing age has increased over the years, including during pregnancy and breastfeeding. Our breastfeeding expert, Dr. Spatz, reviews the evidence for transmission of components of marijuana to breastmilk and what that means for babies who are being breastfed.